Hypothalamic BOLD response to glucose intake and hypothalamic volume are similar in anorexia nervosa and healthy control subjects - Van Opstal, Anna M.; Westerink, Anne M.; Teeuwisse, Wouter M.; van der Geest, Mirjam A.; van Furth, Eric F.; van der Grond, Jeroen (Frontiers in Neuroscience, 2015)
Background. Inconsistent findings about the neurobiology of Anorexia Nervosa (AN) hinder the development of effective treatments for this severe mental disorder. Therefore the need arises for elucidation of neurobiological factors involved in the pathophysiology of AN. The hypothalamus plays a key role in the neurobiological processes that govern food intake and energy homeostasis, processes that are disturbed in anorexia nervosa (AN). The present study will assess the hypothalamic response to energy intake and the hypothalamic structure in patients with AN and healthy controls. Methods. 10 women aged 18-30 years diagnosed with AN and 11 healthy, lean (BMI <23 kg/m2) women in the same age range were recruited. We used functional magnetic resonance imaging (MRI) to determine function of the hypothalamus in response to glucose. Structural MRI was used to determine differences in hypothalamic volume and local grey volume using manual segmentation and voxel-based morphometry. Results. No differences were found in hypothalamic volume and neuronal activity in response to a glucose load between the patients and controls. Whole brain structural analysis showed a significant decrease in grey matter volume in the cingulate cortex in the AN patients, bilaterally. Conclusions. We argue that in spite of various known changes in the hypothalamus the direct hypothalamic response to glucose intake is similar in AN patients and healthy controls.